Foreign Language Teaching to Students Non-Linguistic Higher Education Institutions - Mukhammedova Ozoda Akhtamovna (Global Scientific Publishing, 2023)
The relevance of the article is due to the constant search for the best way to teach a foreign language, especially when studying at a non-linguistic university. In this article, a special department of the project method, as a promising technology in teaching a foreign language. The theoretical significance of the article is due to the rationale for the use of cross-cultural projects in the learning process.
Keywords: globalization; foreign language information; basic knowledge; communication-oriented